Guanidinium and Mixed Cesium-Guanidinium Tin(II) Bromides Effects of Quantum Confinement and Out-of-Plane Octahedral Tilting - Nazarenko, Olga (Chemistry of materials : a publication of the American Chemical Society, 2019)
Hybrid organic-inorganic main-group metal halide compounds are the subject of intense research owing to their unique optoelectronic characteristics. In this work, we report the synthesis, structure, and electronic and optical properties of a family of hybrid tin (II) bromide compounds comprising guanidinium [G, C(NH2)3 +] and mixed cesium-guanidinium cations: G2SnBr4, CsGSnBr4, and Cs2GSn2Br7. G2SnBr4 has a one-dimensional structure that consists of chains of corner-sharing [SnBr5]2- square pyramids and G cations situated in between the chains. Cs+ exhibits a pronounced structure-directing effect where a mixture of Cs+ and G cations forms mono- and bilayered two-dimensional perovskites: CsGSnBr4 and Cs2GSn2Br7. Furthermore, the flat shapes of the guanidinium cations induce anisotropic out-of-plane tilts of the [SnBr6]4- octahedra in the CsGSnBr4 and Cs2GSn2Br7 compounds. In G2SnBr4, the Sn lone pair is highly stereoactive and favors non-octahedral, that is, square pyramidal coordination of Sn(II). G2SnBr4 exhibits bright broad-band emission from self-trapped excitonic states, owing to its soft lattice and electronic localization. This emission in G2SnBr4 is characterized by a photoluminescence (PL) quantum yield of 2% at room temperature (RT; 75 ± 5% at 77 K) and a fast PL lifetime of 18 ns at room temperature